The Influence of Intrinsic Factors and Release Trials on Site Fidelity and Dispersal of Reintroduced Golden Parakeets (Guaruba guarouba, Aves, Psittacidae) - Marcelo Rodrigues Vilarta; Maria Fernanda Naegeli Gondim; Thaís Tamamoto de Moraes; Monica Furtado; Arnaldo Algaranhar Gonçalves; Luís Fábio Silveira (Diversity)
Reintroducing threatened fauna has been established as a valuable conservation practice despite the obstacles that such projects still face. In avian reintroductions, elevated dispersal of released individuals is one of the main factors preventing the establishment of sizeable populations in target areas. We started reintroducing Golden Parakeets in a protected area in the Amazon Forest, and we faced problems regarding low site fidelity. To address this issue, we tested a new methodological approach named “release trials”, consisting of repeatedly releasing and recapturing individual birds to avoid early dispersion. We address the results of applying this method and the influence that intrinsic factors had on the site fidelity of released individuals. We released seven groups of parakeets with an average first-month site fidelity of 46%. Individuals who underwent more release trials before the group release were more likely to present site fidelity. The level of aggression suffered by resident parakeets was the main factor leading to the dispersion of individuals. Older birds were more likely to suffer higher aggression, but age alone did not explain the result of dispersion. Individuals less aversive to humans and previously paired before release were less likely to disperse. Our results show that every bit of methodological care during pre-release training and individual selection may increase the chance of establishing a group with site fidelity.